2019
DOI: 10.1128/aem.00672-19
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Role and Regulation of a Lactate Permease as Lactate Transporter in Bacillus coagulans DSM1

Abstract: A key feature of Bacillus coagulans is its ability to produce L-lactate via homofermentative metabolism. A putative lactate permease-encoding gene (lutP) and the gene encoding its regulator (lutR) were identified in one operon in B. coagulans strains. LutP orthologs are highly conserved and located adjacent to the gene cluster related to lactate utilization in most lactate-utilizing microorganisms. However, no lactate utilization genes were found adjacent to lutP in all sequenced B. coagulans strains. The stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…For example, it is known that operons associated with lactate metabolism are controlled by the GntR family ( Augustiniene & Malys, 2022 ). Specifically, HTH-type transcriptional regulators ( lutR genes) have been shown to regulate genes involved in lactate utilization ( Wang et al., 2019 ). Thus, strain NS-1 T with fewer GntR genes may exhibit reduced efficiency in metabolizing lactate, which SP3-1 readily metabolizes this by-product of glucose utilization.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is known that operons associated with lactate metabolism are controlled by the GntR family ( Augustiniene & Malys, 2022 ). Specifically, HTH-type transcriptional regulators ( lutR genes) have been shown to regulate genes involved in lactate utilization ( Wang et al., 2019 ). Thus, strain NS-1 T with fewer GntR genes may exhibit reduced efficiency in metabolizing lactate, which SP3-1 readily metabolizes this by-product of glucose utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ATP will not be sufficient for maintaining cell growth and LA export under anaerobic conditions. 17 It has been demonstrated that LA production does not contribute to the ATP economy of the engineered yeast on oxygen-limited chemostat cultures. 33 Glycolysis is the major pathway for ATP generation in homolactic fermentation (Figure 3a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Different from that, the lldR gene is usually located adjacent to lactate utilization genes ( 22 , 62 , 63 , 66 ), but the lldR gene (GJQ69_00910) in C. lactatifermentans is located downstream of a PTS operon which consists of genes encoding PTS enzyme II (GJQ69_00895, GJQ69_00900) and a phosphoryl carrier protein (HPr, GJQ69_00905) ( Fig. 9A ).…”
Section: Resultsmentioning
confidence: 99%